A prototype system to measure X-ray absorption spectra for diagnosis in vivo. (November 2016) - Hu, Bo; Zhang, Xingliang; Ouyang, Qinan; Wu, Xiaomei; Fang, Zheng
Abstract: We presented a new non-destructive test system for recording of X-ray absorption spectra. Its purpose was to investigate X-ray absorption spectral characteristics of organic and inorganic compounds and to explore the potential for biomedical pathological examination in vivo. An X-ray source with a maximum voltage of 80 kV and maximum current of 1 mA was selected for both good penetration and low radiation dose. A cadmium telluride (CdTe) detector was chosen for its wide energy range. Pulse-height analysis of the output of this sensor yielded energy spectra of X-rays that had passed through the sample. We calibrated the sensor with varying X-ray tube voltages and used tungsten X-ray lines to verify its accuracy. Different kinds of powders, aqueous solutions, aluminium alloys, and plastics were used as experimental samples to show their X-ray spectral absorption differences. The instrument had good prospects for further diagnostics combining radiology and tissue optics.